2014
DOI: 10.1590/s2317-64312014000300006
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da associação entre os indicadores de saúde bucal, os aspectos socioeconômicos e crianças com sinais clínicos orofaciais indicativos de respiração oral crônica

Abstract: Objetivo Avaliar se os indicadores clínicos de saúde bucal e sociodemográficos de crianças em idade escolar (8 a 12 anos), em fase de dentição mista, estão associados com a respiração oral. Métodos Foram avaliadas 55 crianças, selecionadas em uma escola estadual do município de Cachoeira do Sul (RS). Após a autorização dos responsáveis, foram realizados exames por uma fonoaudióloga treinada, para a identificação de crianças com sinais clínicos orofaciais, indicativos de respiração oral. Para a realização d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
1
0
1
Order By: Relevance
“…Some authors also emphasize a relationship between mouth breathing and the GI value in children and it is consistent with our results [44]. On the other hand, in their studies with children between the age of 8 and 12 years, Piva et al observed no correlation between gingivitis and mouth breathing [45].…”
Section: Gingivitissupporting
confidence: 93%
“…Some authors also emphasize a relationship between mouth breathing and the GI value in children and it is consistent with our results [44]. On the other hand, in their studies with children between the age of 8 and 12 years, Piva et al observed no correlation between gingivitis and mouth breathing [45].…”
Section: Gingivitissupporting
confidence: 93%
“…These studies were consistent with the current investigation in terms of pre-adenotonsillectomy conditions. In contrast, a study showed that oral breathing is not associated with gingival bleeding [ 20 ]. Sharma et al [ 19 ] and Nascimento Filho et al [ 21 ] reported that oral breathing had no effect on the prevalence and extent of gingivitis unless there were significant amounts of germ in the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…• abertura e fechamento dos dentes da frente devido à pressão insuficiente do lábio superior sobre os incisivos; desenvolver esta doença, especialmente se a dieta for cariogênica, o que pode levar a uma significativa piora no estado bucal (Piva et al, 2014).…”
Section: Relação Com Alterações Dentáriasunclassified